Recent progress on piezoelectric, pyroelectric, and magnetoelectric polymer-based energy-harvesting devices - Costa, Pedro Filipe Ribeiro (2019)
Energy harvesting from the environment based on electroactive polymers has been increasing in recent years. Ferroelectric polymers are used as mechanical-to-electrical energy transducers in a wide range of applications, scavenging the surrounding energy to power low-power devices. These energy-harvesting systems operate by taking advantage of the piezoelectric, pyroelectric, and magnetoelectric properties of the polymers, harvesting wasted environmental energy and converting it mainly into electrical energy. There have been developed different nano- and micro-scale power harvesters with an increasing interest for powering mobile electronics and low-power devices, including applications in remote access areas. Novel electronic devices are developed based on low-power solutions, and therefore, polymer-based materials represent a suitable solution to power these devices. Among the different polymers, the most widely used in the device application is the poly(vinylidene fluoride) (PVDF) family, due to its higher output performance.